The Effect of Turmeric Powder in Drinking Water on Performance of Broiler Chickens - I P. Y. A., Pranata; Astawa, I P. A.; Mahardika, I G. (Jurnal Peternakan Tropika, 2019)
The research aims to determine effect of turmeric powder in drinking water on performance of broiler chickens. This research ws conducted at Candikusuma Village, Melaya District, Jembrana Region for 4 weeks. Complitely Randomize Design with 3 tretments and 3 replication. Treatment A: chicken was given drinking water without tumeric powder, Treatment B: chicken was given drinking water contain 1 g tumeric powder in 1000 ml water and Treatment C: chicken was given drinking water contain 2 g turmeric powder in 1000 ml water. The variables observed were: body weight, body weight gain, feed consumption and feed convertion ratio (FCR). The result of this research showed there are no effect of turmeric powder in drinking water on body weight, weight gain and feed convertion ratio.   Key words: broiler chicken, turmeric powder, body weight gain, FCR.